2021
DOI: 10.1002/adfm.202006635
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Halide Perovskitoid TlPbI3 for Ionizing Radiation Detection

Abstract: Room temperature semiconductor detector (RTSD) materials for γ‐ray and X‐ray radiation are in great demand for the nonproliferation of nuclear materials as well as for biomedical imaging applications. Halide perovskites have attracted great attention as emerging and promising RTSD materials. In this contribution, the material synthesis, purification, crystal growth, crystal structure, photoluminescence properties, ionizing radiation detection performance, and electronic structure of the inorganic halide perovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 102 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…The above-band-gap PL emissions of the two compounds should originate from the processes involving defect levels below the valence band maximum or above the conduction band minimum. Such above-band-gap PL emissions were also observed in other compounds, such as CH 3 NH 3 PbI 3 , 39 CsPbCl 3 , CsPbBr 3 , 40 TlPbI 3 , 41 GaAs 1− x N x 42 and GaAs 1− x P x . 43 The similar PL emission behaviors indicate similar types of defects in the two closely-related compounds.…”
Section: Resultssupporting
confidence: 62%
“…The above-band-gap PL emissions of the two compounds should originate from the processes involving defect levels below the valence band maximum or above the conduction band minimum. Such above-band-gap PL emissions were also observed in other compounds, such as CH 3 NH 3 PbI 3 , 39 CsPbCl 3 , CsPbBr 3 , 40 TlPbI 3 , 41 GaAs 1− x N x 42 and GaAs 1− x P x . 43 The similar PL emission behaviors indicate similar types of defects in the two closely-related compounds.…”
Section: Resultssupporting
confidence: 62%
“…It can be observed in Figure 2g that, HMs obtained with no TEA showed absolutely higher ε′ and ε″ values, which can be attributed to the abundant "polarization centers" caused by defects and heteroatoms. [38] Herein, the X-ray photoelectron spectroscopy (XPS) spectra of HMs obtained by no TEA confirmed that the 800 °C HMs had more defects than 600 °C HMs (Figures S7 and S8, Supporting Information), especially the Zn 2p peaks of 800 °C HMs were widened. [39] Nevertheless, the conductivity of HMs obtained with 8 mmol TEA was a little bit higher than that with 4 mmol TEA, which may be attributed to the pinning effect.…”
Section: Impact Of Respective Ion and Phase Hybridization On Electromagnetic Propertiesmentioning
confidence: 85%
“…However, the results from using this approach are not completely satisfactory due to the tendency of forming multicomponent structures in the quasi-2D phase and creating lattice strain during the formation of low-dimensional (LD) structures. Recently, perovskitoid has been proposed to describe the structures where the PbI 6 octahedra are linked by edge and face sharing or combinations of corner, edge, and face sharing (26)(27)(28)(29)(30)(31)(32). Perovskitoids have the potential to effectively modify 3D perovskite due to its diverse PbI 6 connection styles and high stability.…”
Section: Introductionmentioning
confidence: 99%